Securing Performance of Obligations under International Commercial Transactions as an Object of Legal Unification - A. G. Zenyakina (Московский журнал международного права, 2011)
This article addresses rather interesting aspects of security interests arising under international commercial transactions and in particular covers the following issues: conceptual background of the problems associated with security interests; prerequisites, objectives and methods of international legal unification of security interests, as well as principal recent projects existing in this area of unification.